Правовые основы регулирования численности большого баклана в Украине - Катыш, С.В.; Лугинин, Н.С. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
The Cormorant that showed a significant increase in numbers over the last years has negative influence on wetlands (the Sivash area), lands of the natural-reserve fund (preserves "Obitochnaya Spit", "Big and Small Kuchugury", "Ivanovskie Kuchugury"), fish-ponds ("Motor Sich" association), forest plantations (Mysovskoe forestry on Kerch Peninsula), gas-âóêêøñëû ("Black Sea Oil and Gas"). Legal proceedings of the permit (licence) receiving for a control and regulation of the Cormorant numbers is quite long in time and has a lot of practical peculiarities. The conservancy legislation currently in force does not determine anybody, who should be responsible for the efforts on regulation of the Cormorant numbers, order of priorities and sources of financing of these measures.